2015
DOI: 10.1186/s12887-015-0521-6
|View full text |Cite
|
Sign up to set email alerts
|

Smart pumps and random safety audits in a Neonatal Intensive Care Unit: a new challenge for patient safety

Abstract: BackgroundRandom safety audits (RSA) are a safety tool enabling prevention of adverse events, but they have not been widely used in hospitals. The aim of this study was to use RSAs to assess and compare the frequency of appropriate use of infusion pump safety systems in a Neonatal Intensive Care Unit (NICU) before and after quality improvement interventions and to analyse the intravenous medication programming data.MethodsProspective, observational study comparing the frequency of appropriate use of Alaris® CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
0
16
1
1
Order By: Relevance
“…This high rate of compliance has been shown to be critical to the effective use of smart pumps. [8,18,19] Although our rate of compliance is higher than previously reported rates [12,13], basic infusions, which lack the safety features of the DERS, were still used for 11-16% of infusions. Informal assessment revealed that our library had limited options for intravenous fluid selection that did not match the large variety of fluids being used.…”
Section: Discussioncontrasting
confidence: 51%
“…This high rate of compliance has been shown to be critical to the effective use of smart pumps. [8,18,19] Although our rate of compliance is higher than previously reported rates [12,13], basic infusions, which lack the safety features of the DERS, were still used for 11-16% of infusions. Informal assessment revealed that our library had limited options for intravenous fluid selection that did not match the large variety of fluids being used.…”
Section: Discussioncontrasting
confidence: 51%
“…Other authors have also demonstrated the usefulness of RRTSAs in preventing errors resulting from system failures and consider their implementation in NICUs to be fundamental. 7,10,14,15 Limitations It is also important to consider the limitations of our study. First, this was a multicenter study performed in neonatal units with similar delivery-room newborn care provision (level III-A, according to the Spanish Society of Neonatology).…”
Section: Discussionmentioning
confidence: 99%
“…These authors detected defects in areas as important as the use of ventilation materials and respiratory monitoring (383 audits; adequate overall use: 33.7%), 13 resuscitation materials (296 audits; adequate overall use: 62.5%), 14 or infusion pumps (160 audits; adequate global use: 73.1%). 15 This low percentage of audits without defect should lead us to reflect upon whether our current hospital delivery room protocols are able to ensure the correct and complete preparation of positions used during the care of newborns at the time of their delivery. Current protocols state that specific staff members at each center should periodically review the materials and medications available to ensure the adequacy of the radiant warmer set-up, the avail-ability of enough spare parts for each instrument, and periodic verification of the expiration date of expendable materials and medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10,11] Issues that have been raised in the literature include workarounds like the use of basic infusions that do not employ the drug library dosing limits, improper patient or medication identification during pump programming, and high override rates for soft alerts, all of which negate the safety features of smart pumps. [8,12] The use of an additional alerting system in the ICU environment also raises the concern of alert fatigue and the salience of smart pump alerts, due to suboptimal levels of actionable alerts. [13] As a result of alert fatigue from cognitive overload or densitization with time, responsiveness to smart pump alerts may be influenced by other factors, such as work shift, month, repetitiveness of alerts or work complexity.…”
mentioning
confidence: 99%